IN VIVO RADIOPROTECTIVE EFFECTS OF WHEATGRASS (TRITICUM AESTIVUM) EXTRACT AGAINST X-IRRADAITION-INDUCED OXIDATIVE STRESS AND APOPTOSIS IN PERIPHERAL BLOOD LYMPHOCYTES IN RATS - Shyam, Chandresh; Dhawan, Devinder K; Chadha, Vijayta D (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objectives: The present study was undertaken to investigate the possible protective potential of wheatgrass extract against radiation-induced toxicity in peripheral lymphocytes of rats exposed to a fractionated dose of X-rays. Methods: Effects of the X-irradiation with and without wheatgrass were studied on various parameters in peripheral lymphocytes including antioxidant defense system and apoptosis. Male Sprague-Dawley rats were divided into four different groups: Normal control group, X-ray-irradiated group (21 Gy over a span of 7 days), wheatgrass-treated group (80 mg/100 g bodyweight for 2 weeks), and X-rays-irradiated + wheatgrass-treated group. All the biochemical indices which included lipid peroxidation (LPO), reduced glutathione, reactive oxygen species (ROS), and activities of antioxidant enzymes were investigated in lymphocytes. Terminal deoxynucleotidyl transferase dUTP nick-end labeling assay was carried out to assess the apoptosis in lymphocytes following whole-body X-irradiation. Results: Whole-body X-irradiation to rats resulted in significant increase in LPO with concomitant depression of antioxidant enzymes activities, namely, superoxide dismutase, catalase, and glutathione peroxidise (GPx) in lymphocytes. Further, the present study witnessed a significant increase in the number of apoptotic lymphocytes in the X-irradiated animals. However, wheatgrass supplementation lowered the LPO levels, restored cellular antioxidant status, and provided significant protection against radiation-induced apoptosis. Conclusions: Based on these observations, the present study suggests that wheatgrass extract has the potential to be used as an effective radioprotectant against radiation-induced oxidative stress and apoptosis in peripheral lymphocytes of whole-body X-ray-exposed rats.